2020
DOI: 10.1002/pbc.28392
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19 in pediatric oncology from French pediatric oncology and hematology centers: High risk of severe forms?

Abstract: The rapid spread of the coronavirus disease 2019 (COVID-19) pandemic has rapidly led to the establishment of social distancing measures on a global scale to try to protect the general population as well as patients. 1 An unprecedented wave of dedicated preclinical and clinical research projects has also been launched.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
95
3
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 92 publications
(108 citation statements)
references
References 6 publications
(9 reference statements)
6
95
3
4
Order By: Relevance
“…Fifteen of the patients included in the present study were previously reported recently by de Rojas et al 14 . Initial experiences from Italy (Lombardy), 15 China (Wuhan), 16,17 and Europe suggest a low number and severity of COVID‐19 cases in this patient population, 6 contrary to France, where a higher incidence of critical patients was observed 18 . Although in our case series, majority of patients were asymptomatic (25%) or had a mild course (51.1%), the percentage of critical patients (23.4%) was higher in comparison to the Chinese cohort (3‐10.6%) 3 .…”
Section: Characteristics Nmentioning
confidence: 57%
“…Fifteen of the patients included in the present study were previously reported recently by de Rojas et al 14 . Initial experiences from Italy (Lombardy), 15 China (Wuhan), 16,17 and Europe suggest a low number and severity of COVID‐19 cases in this patient population, 6 contrary to France, where a higher incidence of critical patients was observed 18 . Although in our case series, majority of patients were asymptomatic (25%) or had a mild course (51.1%), the percentage of critical patients (23.4%) was higher in comparison to the Chinese cohort (3‐10.6%) 3 .…”
Section: Characteristics Nmentioning
confidence: 57%
“…The clinical characteristics were milder than those described in adult patients with cancer. On the other hand, as of 16 April 2020, there were 33 confirmed COVID‐19 cases from French pediatric oncology centers, of which five (15%) were admitted to PICU 72 . There were no fatal cases at the time of publication.…”
Section: Comorbiditiesmentioning
confidence: 99%
“…So far no concerning reports have emerged from countries that have been facing the COVID‐19 epidemic such as China, Spain, Italy, and US 4‐7 . Only France reported five patients with severe disease among 33 infected nationally 8 …”
Section: Figurementioning
confidence: 99%